PENGARUH METODE PRAKTIKUM BERBANTUAN MULTIMEDIA TERHADAP HASIL BELAJAR PADA MATERI KOLOID SMA NEGERI RASAU JAYA - Latifah, Luluk; Sahputra, Rachmat; Sartika, Rody Putra (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstrackThis research purpose was to determine the differences of learning result between students were given multimedia assisted practicum method and students were not given the multimedia assisted, and to determine the magnitude of multimedia usages impact to the grade XI students learning result on colloid material in Rasau Jaya Senior High School. The used form of research was quasi experiment, the type of research was Quasi Experimental Design with the research design was Pretest Posttest Control Group Design. The used technique of research was in the form of saturated sample. The sample of the research was 23 grade XI IPA I students as experimental class and grade XI IPA II students as control class. Statistical analysis of pretest data did not show any differences in learning result. Instruments used in the form of tests were pretest and posttest. T-independent result with a = 5% showed that between students were given multimedia assisted practicum method and students were not given the multimedia assisted, there were differences in learning result (0,000 < 0,05). This method gave impact in the amount of 47,42% with high category to the learning result.Key words : Practicum Method, Multimedia, Colloid